Perception of English Stress by Korean Speakers: A Comparative Study of the Three Dialect Groups of Seoul Korean, Chonnam Korean, and North Kyungsang Korean - 정영희 (EONEOHAG, 2016)
The ways the prosodic system of L1 affects the perception of English stress by EFL learners were investigated in the present paper. For the purpose, the perceptions of English stress by the speakers of the three dialect groups of Korean, namely, Seoul Korean, Chonnam Korean and North Kyungsang Korean, were compared. The comparison revealed cross-dialectal similarities and differences. Regarding the similarities, the three dialect groups all relied on pitch when perceiving English stress, associating high pitch with stress. However, the dependency on pitch varied across dialects. Thus, when perceiving English stress, speakers of Seoul Korean relied on pitch not only less than North Kyungsang Korean speakers, whose language uses pitch at the lexical level, but also less than Chonnam Korean speakers, whose language uses no lexical tone. On the other hand, Chonnam Korean speakers, whose language has a rising tone on a long vowel at the post-lexical level, showed a tendency to associate a rising F0 contour with stress. KCI Citation Count: 1